SEA SURFACE SALINITY VARIABILITY OF CENTRAL HINDIA OCEANâWEST INDONESIA 1993-2019 - Nabilah, Ghaida
Sea surface salinity is an indicator of the global hydrological cycle and climate variability. Due to limited data over large areas and long periods, it is difficult to see how salinity changes. Surface salinity is influenced by ocean-atmosphere interactions. The western Indonesian region which is directly related to the Indian Ocean is interesting thing to see changes in salinity. Trend analysis was performed on salinity, surface temperature, evaporation, and precipitation data to see the relationship between these parameters. In western Indonesia, for 27 years, the decreasing trend in surface salinity was accompanied by a decrease in evaporation and precipitation trends, while in the Central Indian Ocean, an increase in surface salinity trend was accompanied by an increase in evaporation trend. Surface salinity correlation values are strongly related to evaporation and precipitation, which are 0.62 and -0.47. The results of the calculation of freshwater flux (E-P) in the study area are negative, meaning that precipitation is stronger than evaporation. Calculation of EOF on salinity values in the Indian Ocean and Indonesia is to describe the spatial and temporal patterns of variability. The results of the temporal pattern were cross correlated with the phenomenon index (AUSMI, WYMI, DMI, ONI, WNPMI). In the Indian Ocean, EOF output of the 3 modes is describes 62.6% of the total variance. Modes 1 and 3 EOF have a strong and significant correlation with monsoons, then Mode 2 correlates with IOD. In Indonesia, describes 3 modes with a total 67.1% of the total variance. Modes 1 and 2 correlate with monsoon and Mode 3 with ENSO. Surface salinity anomaly in the Indian Ocean, Mode 1 of 38.3% influenced by monsoon velocity at AUSMI, Mode 2 is 14.6% influenced by IOD, and Mode 3 is 9.7% influenced by monsoon wind speed at WYMI. Salinity anomaly variations in Indonesia with Mode 1 of 43.8% and Mode 2 of 15.2% are influenced by the monsoon velocity at AUSMI and WNPMI then Mode 3 is 8.1% influenced by IOD and monsoon wind velocity at WYMI